A half century of Federal Reserve policymaking, 1914-1964 - Anderson, Clay J.; Federal Reserve Bank of Philadelphia (Philadelphia : Federal Reserve Bank of Philadelphia, 1965)
This book contains the official records of policy making discussions of the Federal Reserve authorities which was meant to be available to scholars and students of central banking.
Study based on the minutes of the meetings of the various policymaking bodies.
Includes bibliographical footnotes and index
usc 20/09/18
Loans
Keywords: Monetary policy